2012
DOI: 10.1017/s1431927612013463
|View full text |Cite
|
Sign up to set email alerts
|

Ionoluminescence in the Helium Ion Microscope

Abstract: Ionoluminescence (IL) is the emission of light from a material due to excitation by an ion beam. In this work, a helium ion microscope (HIM) has been used in conjunction with a luminescence detection system to characterize IL from materials in an analogous way to how cathodoluminescence (CL) is characterized in a scanning electron microscope (SEM). A survey of the helium ion beam induced IL characteristics, including images and spectra, of a variety of materials known to exhibit CL in an SEM is presented. Dire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 30 publications
2
34
0
Order By: Relevance
“…However, ionoluminescence studies are significantly complicated by the fact that an ion beam not only induces light emission, but also directly influences the luminescence properties of the target due to defect creation [49,50] …”
Section: Photonsmentioning
confidence: 99%
See 4 more Smart Citations
“…However, ionoluminescence studies are significantly complicated by the fact that an ion beam not only induces light emission, but also directly influences the luminescence properties of the target due to defect creation [49,50] …”
Section: Photonsmentioning
confidence: 99%
“…It is similar to the cathodoluminescence (CL) phenomenon in scanning electron microscopy (SEM). The possibility for IL studies using HIM was previously demonstrated by Boden et al [50] and Ogawa et al [103]. Ionoluminescence is a result of the radiative relaxation of target electrons that have been excited by the incident beam.…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations